Green Synthesis of Zinc Oxide (ZnO) Nanoparticles: A Review - Abu Bakar Sidik, Dilaeleyana (Multidisciplinary Applied Research and Innovation, 2021)
The agglomeration of nanoparticles (NPs) could be stabilised by the addition of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG) during synthesis of nanoparticles. However, there are some limitation including producing risky by-products and need extensively treated before discharged to the environment. Therefore the development of a greener approach have received a lot of attention from the scientific researchers. The green synthesis of Zinc oxide (ZnO) nanoparticles using plant extracted are still lacking. This review article summarize the information on the application of green capping agent for the synthesis of ZnO nanoparticles. Some researchers are investigating the synthesis of the nanoparticles using various methods, such as physical, chemical and biological. It entails a high cost of equipment, a high temperature and pressure for the physical procedure and requires enormous space for installing the machine. The chemical methods for synthesizing nanoparticles mostly involve the usage of toxic chemicals which is very harmful to the society and environment.